Savings Factors Affecting Confidence of commercial Bank’s officers in Luang Prabang - VANHNALATH, Khanty; KEOBOULAPHETH, Soulideth; PHOUNNALY , Phayvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The objective of the study is to (1) Types and benefits of savings of commercial Bank’s officers in Lung Prabang. (2) Savings factors affecting confidence of commercial Bank’s officers in Lung Prabang. The primary data was collected by conducting questionnaires from 210 samples in Luang Prabang. The study applied Logistics Regression Model to analyze the data. The research results show that types of savings of commercial Bank’s officers mostly prefer making savings at the bank each month. The savings ratio is less than 20% of monthly total income. The average amount of savings is between 500,001 to 1,000,000 kip. The savings money model in commercial bank by saving deposits and fixed deposits account as reason given appropriate return and low risk. Majority of the savings in real estate is buying lands. The purpose of the savings mentioned is just for emergency cases and retirement age. The trend of savings is increasing in the future with savings period for medium-term (1-5 years). This recognition of the benefits for savings from the electronic communication and advertisements of the institution via website and social media. Saving factors affecting confidence of Commercial Bank’s officers in Luang Prabang which consisted of eight factors such as: 1) Asset level of Bank’s officers, 2) Tax level of government, 3 ) Money supply in economics system, 4) interest and of return rate level, 5) level of targeting or planning of bank’s officers, 6) level of advertising and incentives of financial institutions, 7) Age of bank’s officers and 8) Level of education in Bachelor's Degree had statistical significance at the level of 0,1 as they given appropriate return and low risk. As the results, in order to build confidence for future savings; the government, financial institutes and customers need to define eight factors of savings studies appropriately. This will later increase the saving amount.